The Analysis Of Minimum Marriage Age Determination In Indonesia And Other Islamic Countries - Nur Azizah (Jurnal Ilmiah Al-Syir'ah, 2018)
The age of marriage is always a polemic in the household. This is based on the view that the age of marriage that is not mature mentally, physically, psychologically, and education is susceptible to unstable attitudes in taking policies or decisions. So that it is feared that they have not been able to respond to problems in the marriage. Indonesia is a country with Muslims as a major population regulating the minimum age of marriage, as well as Muslim countries in the world. The research method used is the juridicalnormative approach. There are someconclusions obtained. First, the Shari'a does not explicitly set a minimum age for marriage, but legal age and understanding are elements that must be fulfilled for prospective brides, and especially for husbands who are positioned as heads of families. Second, every Islamic country, including Indonesia, has different rules regarding the minimum age of marriage, but the purpose of the restriction remains the same, which is to form a partner who is physically and resourcefully ready to build a sakinah household.Keywords: Rules; Age; Marriage